Assessment of the application for renewal of authorisation of l‐isoleucine produced by Escherichia coli FERM ABP‐10641 as a nutritional additive, its extension of use in water for drinking and a new use as flavouring additive for all animal species. (28th February 2020) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐isoleucine produced by Escherichia coli FERM ABP‐10641 (i) to renew the authorisation and to extend the use of the additive in water for drinking when used as a nutritional additive for all animal species and (ii) to evaluate a new use as a flavouring additive for all animal species. The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. l ‐Isoleucine does not give rise to any safety concern regarding the production strain and its genetic modification. Considering that the production process has not been substantially modified and that no adverse effects have been reported in the literature search, the FEEDAP Panel considers that there is no evidence to reconsider the conclusions reached in previous assessments. Therefore, the Panel considers that the additive l ‐isoleucine produced by E. coli FERM ABP‐10641 remains safe for the target species, consumer and for the environment when used as a nutritional additive in feed. The Panel extends these conclusions to the use of the additive as a flavouring compound. Regarding the use in water, the FEEDAP Panel reiterates its concerns over the safety for the target species of l ‐isoleucine administered simultaneously via water for drinking and feed owing to the risk of nutritional imbalances and hygienic reasons. l ‐Isoleucine is not irritant to skin and eyes and is not a dermal sensitiser but is hazardous by inhalation. The Panel confirms the previous conclusions that the additive is considered as a source of available isoleucine for non‐ruminant animal species when used as a nutritional additive. It requires protection against degradation in the rumen to be as efficacious in ruminants as in non‐ruminant species. The Panel considers the use of the additive in water for drinking to be equally effective than the use in feed when used as a nutritional additive. Since l ‐isoleucine is used in food as a flavouring compound, and its function in feed is essentially the same as that in food no further demonstration of efficacy is necessary.